1997
DOI: 10.1164/ajrccm.155.3.9117003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rhinovirus RNA in lower airway cells during experimentally induced infection.

Abstract: Rhinovirus (RV) infections are presumed to be localized to the upper airway, yet can cause severe lower airway symptoms in children and adults with asthma. To test the hypothesis that rhinovirus infection of the upper airway may be associated with the presence of virus in lower airway cells, we used the techniques of reverse transcription-polymerase chain reaction (RT-PCR) and Southern blotting to detect RV RNA in lower airway cells from eight allergic volunteers experimentally infected with RV16. Bronchoscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
161
0
6

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(177 citation statements)
references
References 18 publications
8
161
0
6
Order By: Relevance
“…Rhinovirus RNA has recently been detected in bronchial lavage cells taken during experimentally induced colds, suggesting that rhinovirus can promote local inflammation by direct infection of the lower airways (13). Indeed, rhinoviruses are capable of prolonged, noncytolytic infection of respiratory epithelial cells and induce production of proinflammatory cy-tokines such as IL-6, 1 IL-8, and granulocyte-macrophage colony-stimulating factor (14 -17).…”
mentioning
confidence: 99%
“…Rhinovirus RNA has recently been detected in bronchial lavage cells taken during experimentally induced colds, suggesting that rhinovirus can promote local inflammation by direct infection of the lower airways (13). Indeed, rhinoviruses are capable of prolonged, noncytolytic infection of respiratory epithelial cells and induce production of proinflammatory cy-tokines such as IL-6, 1 IL-8, and granulocyte-macrophage colony-stimulating factor (14 -17).…”
mentioning
confidence: 99%
“…One possibility is that airway cytokines produced by the upper airway during infection can produce lower airway inflammation [7]. However, a study has reported that rhinovirus ribonucleic acid (RNA) can be detected in the lower airway by PCR after experimental nasal rhinovirus inoculation, suggesting that rhinovirus can directly infect the lower airway [8].…”
mentioning
confidence: 99%
“…Several studies attest to the ability of RV to infect the lower airways, supporting the notion of RV involvement in COPD exacerbations (9)(10)(11). RV readily infects airway epithelial cells from normal subjects in vitro, inducing the expression of such inflammatory mediators as IL-8, GRO-a, ENA-78, IL-6, and TNF-a (12)(13)(14)(15).…”
mentioning
confidence: 73%